1979
DOI: 10.1161/01.str.10.5.560
|View full text |Cite
|
Sign up to set email alerts
|

Body fluid oxygen tension and prognosis in patients with ruptured aneurysm.

Abstract: SUMMARY Body fluid gas pressure and electrolytes of patients with ruptured aneurysm were continuously analyzed. Intracranial pressure (ICP) was regulated at the level of 120-100 mm H 2 O by cerebral ventricular drainage. There was no significant change in the pH, Pco 2 , Hco;, Na + , K + , Ca + + in the cerebrospinal fluid (CSF) of patients with slight or moderate disturbance of consciousness (lethargic-drowsy state). The P C5f o 2 of the patients with marked disturbances of consciousness (semicoma-coma) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…There are few clues in the literature to estimate the oxygen tension of subarachnoidal tissue, where ALL cells preferentially settle. Some studies have evaluated the oxygen tension within the CSF, with estimated values of approximately 5 to 6% [154,155]. More recently, Sharan et al showed that oxygen tension decreases rapidly from pial vessels to the extravascular space in a rodent model, with oxygen levels as low as 3% 30…”
Section: B) Cxcl12/cxcr4mentioning
confidence: 99%
“…There are few clues in the literature to estimate the oxygen tension of subarachnoidal tissue, where ALL cells preferentially settle. Some studies have evaluated the oxygen tension within the CSF, with estimated values of approximately 5 to 6% [154,155]. More recently, Sharan et al showed that oxygen tension decreases rapidly from pial vessels to the extravascular space in a rodent model, with oxygen levels as low as 3% 30…”
Section: B) Cxcl12/cxcr4mentioning
confidence: 99%